Effect of Chromium(VI) on growth, element and photosynthetic pigment composition of Chlorella pyrenoidosa - Hörcsik, Zsolt (Acta Biologica Szegediensis, 2006)
The effects of Cr(VI) were investigated on the growth rate, element, photosynthetic pigment and amino acid composition of Chlorella pyrenoidosa. Cr(VI) is toxic to Chlorella pyrenoidosa. The influence of chromium on cell density and cell number followed very similar trends, indicating that these growth responses might be correlated. The EC50 value for Cr(VI) were 2.0 mg dm-3, the lethal concentration of chromium appears to be approximately 20 mg dm-3 for Chlorella pyrenoidosa. We have investigated the concentrations of chromium, calcium, magnesium and iron. The cells were fractionated into three fractions: cell wall fraction, membrane fraction, soluble fraction after the cells were disrupted. The amount of metals in whole cells and in each cell fraction was determined. Chromium uptake at each concentration was high within 3 days. Chlorella pyrenoidosa can accumulate chromium mainly (approximately 70%) in the cell wall. The concentrations of chromium and calcium show parallel changes with each other. A higher calcium concentration can be observed along with an increasing chromium concentration, both in the cell wall system and in the whole cells. Iron and magnesium concentration show a decreasing tendency. Cr(VI) caused a changes both in free amino acids and proline content. Both free amino acids and proline content increase with the increasing concentration of chromium. Chlorophyll a and b content show a decreasing , while OH-chlorophylls show increasing tendency. Rate of carotene β and α change grows with the increasing chromium concentration. The toxic properties of Cr(VI) can arise from the possibly free diffusion across cell membranes and strong oxidative potential. The toxicological impact of Cr(VI) originates from the action of this form itself as an oxidizing agent, as well as from the formation of free radicals during the reduction of Cr(VI) to Cr(III) occuring inside the cell.